The Implementation of Augmented Reality in Keraton Kanoman’s Museum - Muhammad Emir Ghiffari; Miftah Amirul Amin; Muhammad Arham Irsyad; Umar Ali Ahmad; R Rogers Dwiputra Setiady; Fussy Mentari Dirgantara; Reza Rendian Septiawan (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2022)
Museums genereally display historical objects such as heirlooms and artifacts. To observe this object more clearly visitors usually touch the display case or even hold the objects directly. The implementation of new normal expected that people avoiding contact either directly and indirectly. This study aims to find an alternative solution for reducing contact in museum, This study aims to implement the Augmented Reality (AR) technologies as one of solution for reducing contact in museums, by implementing it in form of mobile application that using Android operating system supported by Unity AR Foundation and ARCore. This research conducted at Keraton Kanoman in Cirebon City. The results of performances test showed 4 out of 10 objects displayed and running 60 Hz Refresh Rates and 60 fps. While the AR/VR development in Android is still limited due to ARCore incompatibility issue, the device proofed to run smoothly without having significant Refresh or Frame Rates drop